PKM Introduction to Character Education Values for Millennials at Ciracas Adventist Collage - Darwin Hartono; Anco, Anco; Endy Grade, Tampubolon (Jurnal Pengabdian Pancasila (JPP), 2023)
Advances in science and technology bring rapid changes both physically and psychologically. This has positive and negative impacts on every aspect of life, including the behavior or attitudes of society, including the millennial generation as the main users of technological advances. Implementation of teaching and learning activities by developing character values that are considered to be fading, including principles, religion, the spirit of mutual cooperation, citizenship and independent creativity. The values of national character which are starting to fade, especially in the millennial generation, must be immediately addressed comprehensively in order to provide a more positive and dignified impact on the nation by means of education. The method of this activity is that partners are given a basic explanation about the philosophical values of character education, and then a dialogue regarding character education. The results obtained from this activity are increased knowledge and understanding regarding character education which must be applied in one's life starting from small things, by oneself and starting as early as possible.